Detection of Explosive Residues using Nanomaterial-based Sensors: A Review - Chavan, Vilas A.; Bhagat, Devidas S.; Gangawane, Ajit K.; Babu, K. Vijaya; Pansare, Dattatraya; Thorat, Bapu R.; Borade, Ravikumar M.; Chawla, Viney; Chawla, Pooja A. (Current Nanoscience, 2025)
Due to the recent rise in explosive-based terrorism and ecological issues, the invention of good capacity detectors for the identification of explosives has emerged as one of the major thirsts in the scientific community. Due to their unique optical and electrical properties, nanocomposites can meet all of the prerequisites for developing preferential, responsive, easy, and cost-effective sensor nodes for the sensing of various explosives. This study primarily throws light on current developments in explosives detection using nanomaterial-based sensors. In particular, it describes how quantum dots, carbon nanomaterials, monometallic nanomaterials, and bimetallic nanomaterials have been used to detect explosives optically and electrochemically. The accurate and consistent features of the nanomaterials, including their synthesis, the explosive detection technique, and the analytical facets, are all thoroughly examined.
Keywords: quantum dots